Kinetic typography visual approaches as a learning aid for English intonation and word stress / Lim Chee Hooi - Lim , Chee Hooi (2018)
Kinetic typography is a unique form of typographic art and technique of arranging text in animation to make the auditory aspects of a language visible. It expresses meaning of content in a unique and dynamic way. Past studies in this area often centers on the various applications of kinetic typography, but there are limited studies on the application of kinetic typography as a visual aid to represent the auditory aspects of English prosody, particularly in intonation and stress. This research aims to explore and ascertain the effectiveness of kinetic typography as a visual learning aid for English intonation and stress. This study hypothesize that kinetic typography can help ESL students to capture the auditory variations in English intonation and stress more effectively. To validate the hypothesis, a pre-experimentation design has been assigned to acoustically analyze the correlation between the visual in kinetic typography and auditory in English speech. Typography characterization scheme designed by Wong (1995) has been adapted to match the two and used to develop a preliminary structure of kinetic typographic visual aid in an experiment. Twenty-five ESL college students have taken part in the exercise. The t-Test analysis result showed significant differences in the treatment of kinetic typography in learning English intonation and stress. However, due to the limitation of the research, many of the statistic cited and suggestions presented in this thesis are not complete solutions to the question considered. Rather, they are to be recognized as carefully formulated hypotheses, which need to be further investigated by other researchers.